PENGARUH KUALITAS PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN RUMAH PADA PERUMAHAN GRAHA CANDI GOLF SEMARANG - Steffina Puspa Melati; Rodhiyah Rodhiyah; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2013)
The purpose of this research was to determine the effect of product quality, price, and location of the purchase decisions on Housing Graha Candi Golf Semarang. Type of research used in this study is explanatory, the study highlights the effect between the study variables and test hypotheses exist. The sampling method using proportionate stratified random sampling technique. The method of analysis used in this study using simple linear regression, and multiple linear regression with SPSS for windows. The results and discussion can be explained by t test product quality has a positive influence on purchase decisions, ie when the product quality is getting better, the higher the level of purchase decision. Price has a positive influence on purchase decisions, ie when more affordable and competitive price, the higher the level of purchase decision.Location has a positive influence on purchase decisions, ie when the strategic location, the higher the level of purchase decision. While the F test showed that the quality of the product, price and location simultaneously positive influence on purchase decisions, ie the better the quality of the product, price and location of the eyes of consumers, the higher the level of purchase decision. From this analysis also can be seen that the variable is a variable location of the dominant influence on the purchase decision, it can dibuktikkan of regression results in the coefficient beta (β) the most, the location with complete facilities and flood free. The conclusion of this research is that the quality of the product, price, and location of the home purchase decision on Housing Graha Candi Golf included in either category, which was considered by most respondents, the higher the purchase decision.